The C-3 Functionalization of 1H-Indazole through Suzuki–Miyaura Cross-Coupling Catalyzed by a Ferrocene-Based Divalent Palladium Complex Immobilized over Ionic Liquid, as Well as Theoretical Insights into the Reaction Mechanism - Jinmeng Yu; Aqun Zheng; Lu Jin; Yong Wu; Qin Pan; Xiangdong Wang; Xiaoyong Li; Wanqin Wang; Min Gao; Yang Sun (Applied Sciences, 2023)
The C-3 functionalization of 1H-indazole could produce a lot of highly valuable pharmaceutical precursors, which could be used for the treatment of cancer and many other inflammatory diseases. This work was focused on the C-3 functionalization of 1H-indazole through Suzuki–Miyaura cross-coupling of 3-iodo-1H-indazole with organoboronic acids, catalyzed by various palladium catalysts immobilized over imidazolium ionic liquids, as well as catalyst recycling. A series of reaction parameters, including the substrate, catalyst, and ionic liquid, were fully investigated. It is significant to note that the yields of the present Suzuki–Miyaura cross-coupling were mainly determined by the catalyst and the solvent used, more than the chemical structure of the substrate. Furthermore, ferrocene-based divalent palladium complexes showed better catalytic outputs compared to simple palladium salts. Moreover, using two imidazolium ionic liquids, BMImX (BMIm+ = 1-n-butyl-3-methylimidazolium, X− = BF4−, PF6−) not only improved the yields of cross-coupled products, but also avoided the formation of Pd(0) black, as compared to the non-ionic liquid facilitated reactions, and simultaneously making catalyst recycling more effective. On average, BMImBF4 performed better than BMImPF6. Additionally, scientific calculations revealed that 1,1′-bis(diphenylphosphino)ferrocene-palladium(II)dichloride dichloromethane complex (PdCl2(dppf)) showed a lower energy barrier in the formation of intermediates than [1,1′-bis(di-tert-butylphosphino)ferrocene]dichloropalladium(II) (PdCl2(dtbpf)), leading to higher catalytic outputs. This work may contribute to the development of 1H-indazole-derived new pharmaceuticals.